TINDAK KEKERASAN TERHADAP TOKOH PEREMPUAN DALAM KUMPULAN CERPEN SAGRA KARYA OKA RUSMINI - Rahayu, Sri; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2014)
The aim of research was to describe the types, the causes, and the effect of violence against the female figures in the collection of short stories Sagra written by Oka Rusmini. This was a qualitative research which used descriptive analysis method. The data of the research was in the form of words, sentences and dialogs related to the types, causes and effects of the violence against the female figures in the collection of short stories Sagra written by Oka Rusmini involving characterization, settings, themes and plots elements. Based on the result of data analysis and discussion, it was concluded that theree were there kids of violence occurred in the collection of short stories including physical and sexual abuses, and economic negligence which had made women suffered from mental pressure. Furthermore, the violence was triggered by the external factors such as those relat5ed to husband and wife authorities, and discrimination of gender in a society. The effect of the violence against the female figures was the physical or mental disadvantages. This was chosely related to the physical condition of the respective female figure.